Capturing the Diversity and Commonalties of Community Engagement - Tiwari, Reena; Lommerse, Marina; Smith, Dianne (Springer, 2014)
Models and methods of engaging communities are greatly influenced by scale and the type of project, by the nature of the communities that are shaped by their locale, and by the disciplinary perspectives of the researchers. Are there any common threads that can be untangled from this web of diversity within which researchers, communities and projects operate?This chapter provides a visual chronicle of all the community engagement narratives that have been presented in Part I. Researchers (authors of Part 1 chapters) workshopped together to compare and contrast the uniqueness of the approaches, models and methods used during the course of their projects. The aim of this chapter is to explore and present the diversities and commonalities embedded in these approaches.